From Händel to Corghi: timbral dramaturgy in Rinaldo & C. (Itinera, 2020)
This essay starts from a fundamental question: can orchestration take on specific dramaturgical functions in musical theatre? The answer is affirmative, provided that it falls within a rational project like the other musical components. In order to define the function of orchestration in Azio Corghi's Rinaldo & C. (1997), a rewriting of Handel's Rinaldo, the analysis first addresses the relationship between the “script” created by the composer himself and the dramaturgy of astonishment, inherited from the late Baroque model. The instrumental characterization of the characters derives directly from it. A fundamental function is performed by the vocal octet, often used in an instrumental way. In Rinaldo & C. the orchestration and development of textures act as an analytical filter of the original model.
Keywords: Corghi; Händel; Rinaldo; Orchestration